A Linguistic Analysis of Derivational Suffixes in Short Story Entitled “The Nightingale and The Rose” by Oscar wilde - Ni Kadek Kesia Lastari; Ida Bagus Gede Nova Winarta (Universitas Islam Negeri Palopo, 2025)
This study aims to analyze the types of derivational suffixes found in the short story The Nightingale and the Rose by Oscar Wilde. The background of this research lies in the importance of understanding word formation processes through derivational suffixes in literary texts, which enrich the meaning and function of words. This research uses a descriptive qualitative method with documentation as the data collection technique. The data was taken from the eBook version of the story, downloaded from Project Gutenberg. The analysis is based on the theories of Plag (2003) and Katamba (1993), who classify derivational suffixes into four types: nominal, adjectival, verbal, and adverbial. The results show that there are 53 derivational suffixes found, consisting of 24 adjectival (45.29%), 19 nominal (35.85%), 10 adverbial (18.87%), and 0 verbal (0%) suffixes. Adjectival suffixes are the most dominant, indicating that descriptive elements and characterization are central to the narrative. In conclusion, the use of derivational suffixes, especially adjectival ones, plays a significant role in shaping the stylistic and morphological richness of the literary text.